Historical institutionalism and policy capacity in analysing the policy failure of Indonesia’s free education - Tri Handoko; Wahyu Zuli; Atikah Nur Pajriyah (Universitas Airlangga, 2026)
This paper explains why Indonesia’s 12-year free education policy continues to experience high drop-out rates and illegal school levies, arguing that these outcomes arise from the interaction between historical-institutional legacies and contemporary policy capacity deficits. The study adopts a qualitative case study design, applying a dual framework of historical institutionalism and policy capacity. It uses secondary data and policy documents to trace path dependence in education financing and to assess analytical, organizational and political dimensions of state capacity.Historical institutionalism analysis shows that systematic underfunding during the Suharto era normalized informal fees and created self-reinforcing sequences that persisted beyond major policy changes. The policy capacity lens reveals weaknesses in problem diagnosis, fragmented budgeting, weak inter-organizational coordination and limited political will to address corruption. Together, these dynamics sustain illegal levies as a parallel financing system rather than a simple implementation failure. The paper offers a multi-theoretical explanation of policy failure by integrating historical institutionalism and policy capacity to show how past underfunding and present capacity deficits jointly reproduce informal financing in Indonesia’s education system. Keywords: education policy, historical institutionalism, Indonesia, policy capacity, policy implementation